Farmers' farm performance is correlated with the dimensions of relationship marketing: a study in Bangladesh - Iris, F.; M. Nawi, N.; Man, N.; Ramli, N. N.; Taj, U. M. (Agricultural Research Communication Centre, 2022)
Background: Nowadays, many individuals are moving toward business relationships, becoming closer and developing business ties with their business partners in the supply chain. Relationship marketing could underpin strategic marketing in minimizing economic problems and enhancing business performance. However, there is little emphasis on how relationship marketing constructs influence paddy farmer’s business, specifically theory-based empirical research. Therefore, the objective of this study is to examine the relationship between relationship marketing components (trust, communication and satisfaction) and paddy farmer’s farm performance in Bangladesh. Methods: A validated survey instrument was used for data collection and 356 paddy farmers were interviewed applying systematic random sampling from the district of Mymensingh in Bangladesh. Partial Least Square Structural Equation Modeling (PLS-SEM) was used in data analysis. Result: The findings revealed that trust, communication and satisfaction had direct relationships with farmers’ farm performance. It was also revealed that satisfaction was a mediator in the indirect relationship between trust and performance. In enhancing farmer’s farm performance, this study suggested that it would be beneficial to practice a long-term relationship marketing strategy instead of a traditional marketing approach in the agriculture context.